Computation of Equilibria in OLG Models with Many Heterogeneous Households - Sebastian Rausch; Thomas F. Rutherford (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
This paper develops a decomposition algorithm by which a market economy with many households may be solved through the computation of equilibria for a sequence of representative agent economies. The paper examines local and global convergence properties of the sequential recalibration (SR) algorithm. SR is then demonstrated to efficiently solve Auerbach-Kotlikoff OLG models with a large number of heterogeneous households. We approximate equilibria in OLG models by solving a sequence of related Ramsey optimal growth problems.This approach can provide improvements in both efficiency and robustness as compared with simultaneous solution-methods.
Keywords: C68; C81; D61; D91; 330; Computable general equilibrium; overlapping generations; microsimulation; sequential recalibration; CGE-Modelling; Allgemeines Gleichgewicht; Dekompositionsverfahren; Overlapping Generations; Theorie